Characterization of the Teleneurology Patients at the Hospital Las Higueras de Talcahuano—Chile - Constanzo, Freddy; Aracena-Sherck, Paula; Peña, Lorena; Marrugo, Mery; Gonzalez, Jonathan; Vergara, Gerardo; Alvarado, Cristóbal (Frontiers in Neurology, 2020)
BACKROUND: Chile has a shortage of medical experts, including neurologists. The remote neurology programme at Las Higueras Hospital in Talcahuano (HHT) was implemented in 2015 to decrease the number of patients waiting for their first appointment. METHODS: This retrospective study analysed a cohort of 2,904 ambulatory patients evaluated in the teleneurology programme at the HHT between 2015 and 2019 who were referred from sixteen primary and three tertiary health care centres. RESULTS: Out of the 2,904 patients included in the study, 1020 patients (35%) were male, and 1884 (65%) were female. In total, 1346 (46.0%) patients were under 60 years old (408 male and 938 female), and 1558 (54%) were over 60 years old (612 male and 946 female). The patients were referred to a neurologist in the teleneurology programme from different primary health care centres (93.5%) and tertiary health care centres (6.5%). The most common diseases diagnosed through teleneurology were, in decreasing order, headache (29.4%), Alzheimer's disease and other dementias (15.9%), and epilepsy (11.4%). From July 2018, we analysed the patient’s destination after the first teleneurology consultation. In the cohort of 634 patients who had their first consultation via the teleneurology programme, 547 (86.3%) were instructed to continue follow-up via telemedicine. CONCLUSIONS: Data from this study show for the first time in Chile, the significant contribution of the teleneurology programme at the HHT to the diagnosis of a broad range of diseases in a substantial number of patients referred from primary and tertiary health care centres.